2009
DOI: 10.1590/s0037-86822009000300019
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous occurrence of brain tumor and myeloradiculopathy in schistosomiasis mansoni: case report

Abstract: Simultaneous occurrence of brain tumor and myeloradiculopathy in cases of Manson's schistosomiasis have only rarely been described. We report the case of a 38-year-old man who developed seizures during a trip to Puerto Rico and in whom a brain tumor was diagnosed by magnetic resonance imaging: brain biopsy revealed the diagnosis of schistosomiasis. He was transferred to a hospital in the United States and, during hospitalization, he developed sudden paraplegia. The diagnosis of myeloradiculopathy was confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Recently, as we were studying human neuroschistosomiasis, we began to suspect that the manifestations in mice may be signs of brain involvement 12,13 . Surprisingly, Schistosoma mansoni eggs and granulomas were identifi ed in the CNS of symptomatic animals.…”
Section: Conflict Of Interest Financial Supportmentioning
confidence: 99%
“…Recently, as we were studying human neuroschistosomiasis, we began to suspect that the manifestations in mice may be signs of brain involvement 12,13 . Surprisingly, Schistosoma mansoni eggs and granulomas were identifi ed in the CNS of symptomatic animals.…”
Section: Conflict Of Interest Financial Supportmentioning
confidence: 99%
“…Patients may present with acute encephalitis or myelopathy or both during the acute phase of the disease after systemic manifestation or during the early stages of chronic disease [7,13,[26][27][28]. Cerebral schistosomiasis involvement occurs more frequently in S. japonicum infections while myelopathy is more common in S. mansoni and S. haematobium infections [26][27][28].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Brain magnetic resonance (MR) imaging showed a left frontalparietal lesion with the "arborized" appearance firstly described by Sanelli et al 67 Brain biopsy confirmed the schistosomal infection, and the patient was treated with praziquantel and dexamethasone. Lambertucci et al 68 reported the case of a 38-year-old American citizen who lived in Brazil and developed seizures during a trip to Puerto Rico. Brain MR imaging showed a large hyperintense tumoral lesion in the right frontalparietal lobe, and brain biopsy yielded the diagnosis of CS.…”
Section: Encephalomyelitismentioning
confidence: 99%
“…In addition, spinal atrophy can be observed in patients having a longer disease course. 68,73,79 Although sensitive, these abnormalities are not specific for SMR.…”
Section: Diagnostic Criteriamentioning
confidence: 99%